FORMATION OF CREATIVE IMAGINATION IN PRESCHOOL CHILDREN - Yarmatova Sevara Tolibovna (Scholar Express Journal, 2023)
At the center of any game and game activity is the opportunity for the child to reflect and repeat the activities and interactions of adults in a unique way. Accordingly, the game acquires social importance, it provides an opportunity for the child to learn valuable knowledge, practical skills, skills and habits created by mankind over the centuries, as a result, it brings him to the essence of interpersonal communication. It will be discussed about the formation of creative imagination in preschool children.
Keywords: preschool children; imagination; interpersonal communication